Pembelajaran Problem Based Learning Menggunakan Konteks Wisata untuk Meningkatkan Pemahaman Konsep Siswa - Balqis, Reka; Elly, As; Umam Zaid Nugroho , Khathibul (AB-JME: Al-Bahjah Journal of Mathematics Education, 2024)
This study aims to see the impact of mathematics learning with the Problem Based Learning Model using a tourism context. Data collection was carried out using the Systematic Literature Review (SLR) method. The steps are research questions, selection criteria, develop search strategies, select studies, the quality of studies, synthesis results related to mathematics learning that are relevant to this study. 12 relevant articles from 40 articles used in this study were obtained from Publish or Perish, Google, Google Scholar. Based on the 12 selected articles, it can be concluded that the application of the Problem Based Learning (PBL) Model in mathematics learning with a tourism context has a positive impact on students' understanding. The use of a tourism context allows students to be more involved and motivated in the learning process, and helps them relate mathematical concepts to real situations around them. This also shows an increase in critical thinking skills and conceptual understanding among students.